SCALE DEVELOPMENT: EMPOWERMENT OF PERSON WITH DISABILITY - , Avantika, Saroj Kumar, Sanjeev Kumar Singh (International Journal of Advanced Science and Technology, 2020)
“A hero is an ordinary individual who find the strength to persevere and endure inspite of overwhelming obstacle”. Person with disability proves an appropriate simili to the above quote. They are empowering themselves day by day by removing “DIS” from their “ABILITY”. It is important to note that we are equally committed to empower them as they form an integral part of society. The main objective of the study was to develop the scale that measures the empowerment of persons with disability and its indicator in Lucknow city. Out of 300 questionnaires employed, 263 received and only 247 were used for the study. This study is descriptive and cross-sectional in nature. Outcome of this study recommends that the newly developed scale is a reliable and valid measure of empowerment of persons with disability. Second order confirmatory factor analysis of the 15-item scale recommends that empowerment of persons with disability should be measured along three dimensions i.e. education and literacy, economic and decision making. This study will provide the sound base to measure the empowerment of persons with disability towards formulating the strategies for inclusive growth and development.